Subjective cognitive complaints in Chinese‐ and English‐speaking older adults. (31st December 2021) - Li, Clara; Zeng, Xiaoyi; Yang, Xiao; Zhu, Carolyn W; Neugroschl, Judith A.; Aloysi, Amy; Cai, Dongming; Martin, Jane; Sewell, Margaret; Loizos, Maria; Greenberg, Jonathan; Xu, Mengfei; et al.
Abstract: Background: Research increasingly suggests that subjective cognitive complaints (SCC) in cognitively healthy older adults may be a harbinger of cognitive decline and dementia. However, there is virtually no investigation on SCC across language groups (English and Chinese). This study examines SCC in Chinese American older adults who are monolingual Chinese speakers. This population has a high risk of being misdiagnosed with cognitive loss and dementia due to cultural and language barriers. Method: The Alzheimer's Disease Research Center at Icahn School of Medicine at Mount Sinai evaluates diverse older adults using the National Alzheimer's Coordinating Center's Uniform Data Set. Each participant receives a research diagnosis of normal control, mild cognitive impairment, and dementia at consensus. SCC was measured by the Cognitive Function Instrument (CFI). The instrument covers changes in cognition with yes(1)/no(0)/maybe(0.5) as available responses. Total score ranges from 0 to 14, with higher scores indicating greater SCC. The development of Chinese version of CFI was modeled after a protocol for multinational translations, which includes two independent forward translations and a back translation. Multivariate analysis of variance was conducted to examine group differences in SCC using CFI scores as dependent variables, while accounting for age, gender, and education. Result: Data analysis included English‐ (n=63) and Chinese‐speaking older adults (n=30) who received a diagnosis of normal cognition, with no psychiatric symptoms/diagnosis at consensus. The two groups did not differ in age (Chinese=73.43+ 6.83 years; English=74.75+ 7.12 years) and gender (Chinese=70.0% female; English=65.1% female), but Chinese‐speaking older adults (13.83+ 3.12 years) had lower levels of education compared to English‐speaking older adults (16.49+ 2.47years). Results show that Chinese‐speaking older adults endorsed more SCC (3.52+ 2.68 items) than English‐speaking older adults (1.74+ 1.67 items) (p<0.01). For 7 of the CFI items (i.e., rely more on written reminders, need help to remember appointments, trouble driving, less social, trouble following news/TV/books, difficulty with hobbies/activities, become disoriented/get lost), frequency of endorsement was higher in Chinese‐speaking older adults than English‐speaking older adults (p<0.05). Conclusion: Our findings highlight potential differences in SCC reported by Chinese‐speaking older adults who have immigrated to the USA. A longitudinal follow up is needed to evaluate contributing factors to such differences.